Seeding Date Effects on Camelina Seed Yield and Quality Traits - E. Obeng; A. Obour; N. O. Nelson (Kansas Agricultural Experiment Station Research Reports, 2016)
An alternative crop with potential for dryland crop production in the Great Plains is camelina (Camelina sativaL.Crantz). Time of planting is an important management consideration that can affect camelina production. A study was carried out in the spring of 2013, 2014, and 2015 to evaluate seeding date effects on spring camelina varieties grown under dryland conditions in western Kansas. Three spring varieties (Blaine Creek, Pronghorn, and Shoshone) were planted at three seeding dates: early (April 3, 2013; March 17, 2014; and March 18, 2015); mid (April 16, 2013; April 1, 2014; and April 1, 2015); and late (April 30, 2013; April 15, 2014; and April 15, 2015). Parameters collected included time of flowering and physiological maturity, stand count at maturity, seed yield, biomass yield, harvest index, oil and protein content. Our findings indicate that seeding date can affect the time of flowering and physiological maturity, stand count, seed yield, biomass yield, harvest index, and protein content, but it did not affect oil content. Harvest index and oil content was significantly different among varieties. In general, mid and late seeding dates produced the highest yield across the three years. There were yield differences among varieties; Blaine Creek produced the highest seed yield and was significantly different from Pronghorn and Shoshone. Seed yield ranged between 340 and 440 lb/a. Average oil and protein content was 26% and 30%, respectively. Based on environmental factors and agronomic characteristics, camelina varieties were more productive when planted between early and mid-April.
Keywords: Camelina; variety; seeding date; quality traits